Environmental Tendencies and Practices of Secondary School Students On-Field Study, Lattakia City - Yasin, Ahlam (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
This piece of research aims to identify the environmental tendencies and practices of secondary school students throughout the schools of the City of Lattakia. To achieve this, the researcher prepared a questionnaire of of 40 points in order to measure them; this follows the confirmation of the tool’s authenticity and loyalty. The study specimen includes 200 fe/male students over two study groups: the 10th calss and the 11th class (scientific and literary branches) and the 12th class (scientific and literary branches) to trace the disparity among averages, and their various inherent levels. The adopted law of t-test is the Analysis of Variance Tests. Research findings verify: the existence of a statistical difference between male students’ orientations and female students’ orientations toward environment where females score higher; the existence of statistical difference between the environemental tendencies and practices where tendencies are higher. Findings also reveal the absence of a significant difference between tendencies and practices of secondary school students toward environment and the environmental education due to the variance of the teaching class; however, the scientific or literary specialization affects the environmental tendencies and practices to the benefit of the literary branch students. This can be ascribed to the apparent shortage of students’ information and cognizance about environment and the current status of the environmental education in addition to the increase of the environmental problems and their effect on human health. Thus learning is viewed as the right entrance to education in general and to environmental education in particular, and one basis for achieving the environmental awareness, and the change of behaviour and values to cope with the demands of sustainable development.